Scientific and methodological support of training athletes of russian national teams: yesterday, today, tomorrow - G.P. Bryusov; A.S. Kryuchkov; S.L. Horonyuk; V.V. Shiyan (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine ways to improve the system of scientific and methodological support for the training of high-class athletes. Results and conclusions. On the basis of a theoretical analysis of publications, the authors update the discussion in the field of improving the scientific and methodological support for the training of athletes of the Russian national teams. The argumentation of the opinion that there are no grounds for creating new structural divisions and organizations that duplicate the activities of the Center for Sports Training of Russian National Teams, the leading research organization in the field of elite sports, is given.